2012
DOI: 10.1002/path.4012
|View full text |Cite
|
Sign up to set email alerts
|

Frequent activating GNAS mutations in villous adenoma of the colorectum

Abstract: To elucidate the role of GNAS mutations in colorectal tumourigenesis, we performed a mutation analysis in a total of 234 colorectal tumours, including adenomas, serrated lesions and adenocarcinomas. Activating GNAS mutations were found in 20 of the 24 villous adenomas (83%) but were absent in all the other tumours, except for one tubulovillous adenoma (3%) and two adenocarcinomas (3%). KRAS and BRAF mutations were always mutually exclusive. KRAS mutations were frequent in villous (67%) and tubulovillous (60%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
86
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 16 publications
13
86
1
Order By: Relevance
“…14,15,39 which may suggest a possible link at the molecular level to colorectal villous adenoma, where GNAS is commonly mutated (83%). 40 b-Catenin, a downstream target of the growthpromoting Wnt signalling pathway, was recently linked to progression of biliary intraductal papillary neoplasm of the bile duct associated with hepatolithiasis. 25 In our study, nuclear b-catenin accumulation was found only in four intraductal papillary neoplasms of the bile duct in non-invasive lesions.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,39 which may suggest a possible link at the molecular level to colorectal villous adenoma, where GNAS is commonly mutated (83%). 40 b-Catenin, a downstream target of the growthpromoting Wnt signalling pathway, was recently linked to progression of biliary intraductal papillary neoplasm of the bile duct associated with hepatolithiasis. 25 In our study, nuclear b-catenin accumulation was found only in four intraductal papillary neoplasms of the bile duct in non-invasive lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic GNASactivating mutations cause McCune Albright syndrome, pituitary adenomas, endocrine tumors, and/or fibrous dysplasia of bone, primarily through increased cAMP levels, which in some cells can lead to proliferation [16,17]. Activating GNAS mutations have also been frequently observed in gastric and duodenal pyloric-gland adenomas [18], and colorectal villous adenomas and are often associated with KRAS mutations [19]. Interestingly, GNAS and KRAS mutations have been detected in 29 and 32% of intraductal papillary neoplasms of the bile duct respectively (especially those with intestinal differentiation) [20].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…Immunohistochemistry was performed using anti-E-cadherin antibody (NCH-38; 1:100 dilution; DAKO, Glostrup, Denmark) as previously described [8]. The results showed loss of E-cadherin expression in SRCCs.…”
Section: Case Reportsmentioning
confidence: 99%